Correlation between microstructure and mechanical properties of 6061-T6 double-side FSW joint. (February 2019) - Du, Chengchao; Wang, Xue; Pan, Qiuhong; Xue, Kailin; Ni, Mansheng; Liu, Junjian
Abstract: 6061-T6 (6 mm thick) double-side friction stir welding (DS-FSW) joint was fabricated using a stir tool with a pin length of 4.3 mm. The microstructure and mechanical properties of the DS-FSW joint was characterized. The results showed that the texture of shoulder affect zone (SAZ) was {111}<110>. The texture of the pin affect zone (PAZ) was {112}<110> and {111}<110> as the additional shear stress from the thread. During the welding of front-side, the dislocation density and precipitates of the remaining back-side SAZ was improved. The higher dislocation density and more precipitates contributed to a higher hardness of the remaining back-side SAZ. The strength and elongation of remaining back-side SAZ in welding direction were greatly damaged as the poor combination between the deposited metal layers under the thermal and mechanical influences from the welding of front-side. The AS side of remaining back-side SAZ was enhanced under the thermal and mechanical influences from the welding of front-side. The cracking did not occur on the AS side of back-side stir zone (SZ) anymore as the enhanced AS side of remaining back-side SAZ.